Coopetition between organizations in the sports services market - Stosik, Aneta; Leśniewska, Aleksandra (Journal of Education, Health and Sport, 2017)
Research interest in the issues of building the relational capital, relational resources and cooperation between organizations, especially those that compete with each other, is recently seen in the literature of the subject, especially in the sciences of management. Concepts of building a competitive advantage specify various factors, tools, methods and ways of creating them. The aim of the article is to present the results of own research on the identification of cooperation and coopetition with competitors on the market of commercial sports services. The phenomenon of simultaneous cooperation and competition is noticed in the research mainly in the production sectors, while poorly is recognized in the service industries, and especially in sport and recreation. The specifics of cooperation relations and network of relationships leads to different functioning from other partners, which may contribute to the creation of a new quality of functioning, increased innovation supported by creativity, as well as cost reduction. Organizations that provide their services in the sports environment also fit into the phenomenon of resource use, in order to multiply the advantages and create new values for their clients.